Multi-scale pore structural change across a paleodepositional transition in Utica shale probed by gas sorption overcondensation and scanning. (December 2021) - Pitcher, Eleanor G.; Large, David J.; Fletcher, Robin S.; Rigby, Sean P.
Abstract: Pore structure and network configuration in shales greatly impacts physical processes important for hydrocarbon migration, methane extraction, gas storage, or carbon sequestration. The multi-scale nature of the porosity in shales presents significant challenges to its comprehensive and accurate characterisation. The under-used gas overcondensation technique can bridge characterisation of micropores, below the detection limit of mercury porosimetry and many imaging methods, to that of macroporosity undetected by conventional adsorption experiments. Further, gas sorption scanning curves revealed advanced condensation effects that allowed the probing of the inter-relation and juxtaposition of multi-scale porosities. It was found that the changeover period, from primarily clay to carbonaceous deposits in the Utica shale, was associated with growth in the disorder of the pore network over particular key length-scales highlighted by percolation processes in the gas overcondensation and scanning curves. Critical path theory suggests that the marked percolation knee that developed in overcondensation data at the depositional transition would identify a particular pore size that is characteristic of the wider network, and would control mass transport. The peak in pore network disorder was also associated with a peak in total organic carbon content and the accessible porosity was shown to be dominated by the organic carbon phase. Complementary mercury porosimetry combined with computerised X-ray tomography has shown substantial changes in the type, and super-micron-scale spatial distribution, of the nanoporosity down to approximately 3 nm, accessible to mercury, across the depositional transition, probably related to the amount and disposition of carbonate minerals. Highlights: Overcondensation data bridges microporosity and macroporosity in shales. Scanning loops reveal spatial juxtaposition of micro- and macro-pores. Transition in mineralogy, and peak in organic carbon, correspond to occurrence of percolation knee in overcondensation. CXT combined with mercury porosimetry can map nanoporosity at macro-scale.